Profil Cedera Kepala pada Korban Kecelakaan Lalu Lintas di RSUP Dr. M. Djamil Padang 2021-2022: Analisis Deskriptif - Hariyani, Insil Pendri; Putri, Aulia; Nurwiyeni, Nurwiyeni (PT. Riset Press International, 2024)
Head injury is a serious complication often occurring in traffic accident victims, especially in the West Sumatra region. This study aims to analyze the demographic profile, types of injuries, and risk factors among traffic accident victims who suffered head injuries. Data were collected from 50 patients treated at Dr. M. Djamil General Hospital in Padang during the study period. The results show that the majority of victims were male (64%), with late adolescents (17-25 years old) being the most dominant age group (36%). Mild head injuries were the most commonly found (48%), and single-vehicle accidents were the most frequent type of accident (54%). This study highlights the importance of prevention and management of head injuries in high-risk populations in West Sumatra.